Semi-crystal multi-element ceramic coating as well as preparation and application thereof
Through the preparation method of semi-crystal multi-component ceramic coating, the problems of corrosion and cracks of ceramic coatings in high-temperature water vapor environments are solved, high density and chemical stability are achieved, and service life and corrosion resistance are significantly improved.
Patent Information
- Application Number
- CN202510370074.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-06-10
AI Technical Summary
Existing ceramic coatings are prone to corrosion, cracks and peeling problems in high-temperature water vapor environments, and cannot meet the needs of aerospace, advanced energy and other fields for high-temperature hydrothermal corrosion resistance and long service life.
Using the preparation method of semi-crystal multi-component ceramic coating, dense ceramic powder is obtained by ball milling, dissolved in solvent to form a slurry, coated on the surface of the substrate, dried and fired at high temperature to form a coating with high chemical stability and good density.
The high density and chemical stability of the coating are achieved, the porosity and standard protection current are reduced, and the service life and corrosion resistance are significantly improved in hydrothermal environments.
Smart Images

Figure CN120117894A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of corrosion-resistant coatings, and in particular to a semi-crystalline multi-component ceramic coating and its preparation and application. Background Art
[0002] In the development process of high-end technologies such as aerospace and advanced energy, ceramic coatings have become key protective materials due to their excellent properties such as high temperature resistance, wear resistance, and chemical stability. However, the high-temperature steam environment has become a severe challenge for ceramic coatings in practical applications. In the aviation field, a large amount of steam is generated during the combustion of aviation fuel. The high-temperature steam will penetrate into the interior of the coating through defects such as pores and microcracks in the coating, react chemically with the metal substrate, accelerate the corrosion of the metal substrate, and at the same time promote the rapid growth of thermally grown oxides, ultimately resulting in the delamination and peeling of the coating. In addition, the high-temperature steam environment will cause phenomena such as expansion and decomposition of the ceramic coating, resulting in a large number of cracks in the coating, a significant decrease in adhesion, and a serious impact on durability.
[0003] Similarly, in civil and industrial application fields such as the inner liner of water heaters and the inner wall materials of hydrothermal reaction kettles, similar challenges in the hydrothermal environment are also faced. Currently, the coatings for the inner liner of water heaters mostly use materials such as enamel coatings and organic coatings. Although enamel coatings have certain corrosion resistance and wear resistance, bubbles or pinholes are easily generated during the production process of enamel coatings. At the same time, due to their relatively large brittleness, scale explosion is likely to occur during vibration and collision during transportation and installation. And in the long-term high-temperature hydrothermal environment, problems such as coating peeling and cracking are likely to occur. Organic coatings will have their performance degraded due to high-temperature hydrolysis, oxidation, etc., resulting in problems such as coating peeling and protection failure. In addition, metal ions such as magnesium and calcium, as well as dissolved gases such as oxygen and carbon dioxide, will cause electrochemical corrosion. Oxygen will undergo a reduction reaction on the surface of the coating, while the metal elements in the coating will lose electrons and undergo an oxidation reaction, forming a corrosion cell and accelerating the corrosion failure of the coating. In a high-temperature and high-pressure hydrothermal environment, the grain boundaries in the material are prone to become the preferred sites for corrosion. Intergranular corrosion will weaken the bonding force between grains, reduce the strength and toughness of the material, and seriously affect its service life and safety.
[0004] Existing coating materials all have performance defects to varying degrees in the hydrothermal environment and cannot meet the protection requirements of aerospace, advanced energy, and civil industries for stable performance structure, high-temperature hydrothermal corrosion resistance, and long service life. Therefore, it is crucial to develop a semi-crystalline multi-component ceramic coating that is not easily peeled off or bulged, does not easily generate penetrating cracks, and has good densification. Summary of the Invention
[0005] To solve the above problems, the object of the present invention is to provide a semi-crystalline multi-component ceramic coating and its preparation and application. The semi-crystalline multi-component ceramic coating provided by the present invention is not easy to fall off or bulge, and is not easy to generate penetrating cracks, and has good densification (low porosity and high densification); at the same time, it does not undergo chemical reactions, decomposition and aging during the hydrothermal corrosion process, has high chemical stability, and after long-term high-temperature hydrothermal cycling, the integrity of the ceramic coating and the metal substrate and good interfacial bonding force.
[0006] The object of the present invention can be achieved by the following technical solutions:
[0007] The first object of the present invention is to provide a preparation method of a semi-crystalline multi-component ceramic coating, comprising the following steps:
[0008] (S1) Ball-milling 48-52 parts of ZrO 2 , 20-25 parts of SiO 2 , 10-15 parts of CaO, 3-6 parts of TiO 2 , 1-3 parts of K 2 O, 1-3 parts of MnO 2 , 1-3 parts of Fe 2 O 3 , 1-3 parts of BaO, 0.5-1 part of CuO, 0.5-1 part of ZnO, 0.5-1 part of NiO, 0.5-2 parts of boride and 0.1-0.3 part of dispersant to obtain semi-crystalline multi-component ceramic powder;
[0009] (S2) Dissolving the semi-crystalline multi-component ceramic powder prepared in step (S1) in a solvent and mixing evenly to obtain a semi-crystalline multi-component ceramic slurry;
[0010] (S3) Coating the semi-crystalline multi-component ceramic slurry prepared in step (S2) on the surface of a pretreated substrate, and successively performing drying treatment and high-temperature firing treatment to obtain a semi-crystalline multi-component ceramic coating combined with the substrate.
[0011] In one embodiment of the present invention, in step (S1), the boride is selected from one or more of TiB 2 , TiBN, ZrSiB 6 , ZrB 2 , ZrBN, HfB 2 , HfBN, ZrSiBCN, ZrTiBCN, HfZrSiBCN or HfZrTiBCN;
[0012] The dispersant is selected from one or more of polymaleic acid, polyacrylic acid, polycarboxylate or maleic acid-acrylic acid copolymer.
[0013] In one embodiment of the present invention, in step (S1), during the ball milling process, the rotation speed is 1500 - 4000 r / min, and the time is 10 - 15 min.
[0014] In one embodiment of the present invention, in step (S2), the mass ratio of the semi-crystalline multi-component ceramic powder to the solvent is 1:0.3 - 0.4;
[0015] The mixing is carried out by stirring and mixing, and an antifoaming agent is added dropwise during the stirring process. The stirring speed is 300 - 600 r / min.
[0016] In one embodiment of the present invention, the antifoaming agent is selected from one or more of polyoxypropylene ethylene glycol glycerol ether (GPE), polyoxypropylene glycerol ether (GP), polyoxypropylene polyoxyethylene glycerol ether stearate (GPES), polypropylene glycol-based glycerol ether, polyether polyol, or silicone polyether.
[0017] In one embodiment of the present invention, in step (S3), the coating method is the leveling method;
[0018] The pretreated substrate is specifically a substrate that has been subjected to grinding treatment, washing treatment, and drying treatment in sequence.
[0019] In one embodiment of the present invention, grinding treatment is carried out using 400 - 800 mesh metallographic sandpaper to remove the oxide layer on the surface of the substrate;
[0020] Ultrasonic washing treatment is carried out using ethanol, and the ultrasonic washing time is 10 - 20 min;
[0021] During the drying process, the temperature is 50 - 80 °C, and the time is 20 - 60 min.
[0022] In one embodiment of the present invention, in step (S3), during the drying process, the temperature is 100 - 115 °C, and the time is 10 - 20 min.
[0023] In one embodiment of the present invention, in step (S3), during the high-temperature firing process, the temperature is 775 - 850 °C, and the time is 10 - 20 min.
[0024] In one embodiment of the present invention, the thickness of the semi-crystalline multi-component ceramic coating is 100 - 600 μm;
[0025] Preferably, the thickness of the semi-crystalline multi-component ceramic coating is 150 - 300 μm.
[0026] In the present invention, at the initial stage of the preparation process of the semi-crystalline multi-component ceramic coating, the semi-crystalline multi-component ceramic coating covering the surface of the metal substrate is not in a dense state, and there are some pores and cracks. Oxygen can reach the substrate through these pores and cracks and react with the substrate to generate FeO or Fe3 O 4 As the temperature rises, the semi-crystalline multi-component ceramic coating begins to melt and densify, blocking the oxygen transport channels and preventing the oxide film from growing further. At the same time, FeO or Fe 3 O 4 reacts with components such as SiO 2 and B 2 O 3 in the semi-crystalline multi-component ceramic coating to form Fe-Si-O and Fe-B-O composite oxide interface layers. At high temperatures, Fe 2+ / Fe 3+ in the metal matrix diffuses and mixes with Si 4+ and B 3+ in the semi-crystalline multi-component ceramic coating through the interface to form a gradient diffusion layer. The Fe-Si-O structure in the diffusion layer is microscopically bonded to the metal matrix in the form of covalent bonds or ionic bonds, forming chemical anchor points to ensure the tight bonding between the semi-crystalline multi-component ceramic coating and the matrix.
[0027] As a self-healing component, boron atoms in borides can form dynamic covalent bonds, namely borate ester bonds, with oxygen atoms. Under specific conditions, when the material is damaged, the borate ester bonds will break, and substances such as boric acid released can react with other surrounding hydroxyl-containing substances again to form new borate ester bonds, thereby filling the cracks and enabling the material to achieve self-healing through bond recombination after being damaged. In addition, borides are prone to react with oxygen at low temperatures (~500°C) and react with SiO 2 to generate a liquid borosilicate glass phase with good fluidity and adhesion. In a high-temperature environment, the glassy borosilicate can melt and flow to the damaged part of the material to fill and heal the cracks, and form a continuous and dense glass film after cooling, ensuring the mechanical properties and integrity of the material and reducing corrosion damage.
[0028] The second object of the present invention is to provide a semi-crystalline multi-component ceramic coating prepared by the above method. This semi-crystalline multi-component ceramic coating can eliminate defects such as internal through-holes, through-cracks, and grain boundaries in the coating, with a porosity of less than 1.5%. Under long-term hydrothermal conditions, the material also has self-healing and repair capabilities, and the service life in the hydrothermal environment is greatly improved (good mechanical properties).
[0029] The third object of the present invention is to provide an application of the semi-crystalline multi-component ceramic coating in the aerospace field.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) Adding a boride self - healing component to the semi - crystalline multi - component ceramic coating prepared by the present invention can significantly reduce the viscosity of the ceramic in the molten state, which is beneficial to the floating of bubbles, reduce the formation of through - holes in the coating, and effectively improve the density of the coating. Moreover, during the hydrothermal corrosion process, the boride will chemically react with oxygen to generate vitreous borosilicate, repair defects such as cracks and holes in the enamel, and hinder the infiltration of water vapor.
[0032] (2) The standard protection current of the semi - crystalline multi - component ceramic coating prepared by the present invention is as low as 0.059 mA / m 2 , which is two orders of magnitude lower than that of the existing corrosion - resistant ceramic coating (12 mA / m 2 ).
[0033] (3) The semi - crystalline multi - component ceramic coating prepared by the present invention has excellent high - temperature hydrothermal corrosion resistance, greatly improving the service life. Moreover, the preparation process is simple, the maintenance cost is low, and it has broad application prospects. Description of the Drawings
[0034] Figure 1 Fig. is the cross - sectional SEM image of the semi - crystalline multi - component ceramic coating prepared in Example 1 and the traditional ceramic coating prepared in Comparative Example 1;
[0035] Figure 2 Fig. is the SEM image of the surface of the semi - crystalline multi - component ceramic coating prepared in Example 1 and the traditional ceramic coating prepared in Comparative Example 1 after high - temperature hydrothermal corrosion;
[0036] Figure 3 Fig. is the Nyquist diagram of the semi - crystalline multi - component ceramic coating prepared in Example 1 and the traditional ceramic coating prepared in Comparative Example 1;
[0037] Figure 4 Fig. is the Bode diagram of the semi - crystalline multi - component ceramic coating prepared in Example 1 and the traditional ceramic coating prepared in Comparative Example 1;
[0038] Figure 5 Fig. is the XRD diagram of the semi - crystalline multi - component ceramic coating prepared in Example 2 and the traditional ceramic coating prepared in Comparative Example 1. Detailed Embodiments
[0039] The present invention will be described in detail below with reference to the drawings and specific embodiments.
[0040] In the following examples, the high-energy ball milling was carried out using a UNIONPROCESS grinder produced by Qingdao Lianrui Precision Instrument Co., Ltd., with the model number 01-HDDM; the high-temperature box furnace was the Shangguang XLC-1400C box furnace produced by Shanghai Daheng Optical Precision Machinery Co., Ltd.; unless otherwise specified, all reagents used were commercially available reagents, and all detection means and methods used were conventional detection means and methods in the art.
[0041] Example 1
[0042] This example provides a method for preparing a semi-crystalline multi-component ceramic coating, which includes the following steps:
[0043] (S1) The surface of the metal substrate was polished with 400-mesh sandpaper to remove the oxide layer, then ultrasonically cleaned with ethanol for 15 min, and placed in an oven at 80 °C for drying for 20 min to obtain a pretreated metal substrate;
[0044] (S2) 50 parts of ZrO 2 , 23 parts of SiO 2 , 12 parts of CaO, 5 parts of TiO 2 , 2 parts of K 2 O, 1.5 parts of MnO 2 , 1.8 parts of Fe 2 O 3 , 1.6 parts of BaO, 0.8 parts of CuO, 0.7 parts of ZnO, 0.6 parts of NiO, 1 part of ZrSiB 6 and 0.2 parts of polymaleic acid were mixed and then subjected to ball milling treatment (rotation speed: 2000 r / min, time: 10 min). After the ball milling was completed, it was dried to constant weight to obtain a uniformly mixed semi-crystalline multi-component ceramic powder;
[0045] (S3) The semi-crystalline multi-component ceramic powder prepared in step (S2) and pure water were put into a conical flask according to a mass ratio of 1:0.33 and subjected to mechanical stirring treatment (rotation speed: 400 r / min, time: 10 min). During the stirring process, GPE defoamer was added dropwise to obtain a semi-crystalline multi-component ceramic slurry;
[0046] (S4) The semi-crystalline multi-component ceramic slurry in step (S3) was uniformly coated on the surface of the metal substrate prepared in step (S1) by the leveling method; then it was placed in an oven at 110 °C for drying for 15 min, and then placed in a box furnace at 800 °C for high-temperature sintering for 15 min to obtain a high-temperature hydrothermal corrosion-resistant semi-crystalline multi-component ceramic coating with good bonding to the metal substrate and high density, and the coating thickness was about 150 μm.
[0047] Comparative Example 1
[0048] This comparative example provides a method for preparing a traditional ceramic coating, which specifically includes the following steps:
[0049] (S1) Polish the surface of the metal substrate with 400-mesh sandpaper to remove the oxide layer, then ultrasonically clean it with ethanol for 15 min, and place it in an oven at 80 °C for drying for 20 min to obtain a pretreated metal substrate;
[0050] (S2) Mix 50 parts of ZrO 2 , 23 parts of SiO 2 , 12 parts of CaO, 5 parts of TiO 2 , 2 parts of K 2 O, 1.5 parts of MnO 2 , 1.8 parts of Fe 2 O 3 , 1.6 parts of BaO, 0.8 parts of CuO, 0.7 parts of ZnO, 0.6 parts of NiO, and then carry out ball milling treatment (rotation speed is 2000 r / min, time is 10 min). After the ball milling is completed, dry it to constant weight to obtain a uniformly mixed traditional ceramic powder;
[0051] (S3) Put the traditional ceramic powder prepared in step (S2) and pure water into a conical flask according to a mass ratio of 1:0.33 and carry out mechanical stirring treatment (rotation speed is 400 r / min, time is 10 min) to obtain a traditional ceramic slurry;
[0052] (S4) Adopt the leveling method to uniformly coat the traditional ceramic slurry in step (S3) on the surface of the metal substrate prepared in step (S1); then place it in an oven at 110 °C for drying for 15 min, and then place it in a box furnace at 800 °C for high-temperature sintering for 15 min to obtain a traditional ceramic coating with good bonding to the metal substrate, and the coating thickness is about 150 μm.
[0053] Figure 1 SEM images of the cross-section of the traditional ceramic coating ( Figure 1 a) prepared in Comparative Example 1 and the semi-crystalline multi-component ceramic coating ( Figure 1 b) prepared in Example 1. It can be found through Figure 1 that there are a large number of pores in the traditional ceramic coating, which provides an infiltration path for high-temperature water vapor; the thickness of the semi-crystalline multi-component ceramic coating prepared in Example 1 is about 150 μm, and there is a transition bonding layer between the metal substrate and the semi-crystalline multi-component ceramic coating, and a large number of anchor points are formed, indicating that the interface between the semi-crystalline multi-component ceramic coating and the metal substrate is tightly bonded; in addition, almost no spherical pores can be seen in the cross-section of the semi-crystalline multi-component ceramic coating, the coating porosity is greatly reduced, and the density is increased.
[0054] Figure 2 SEM images of the surface of the traditional ceramic coating ( Figure 2 a) prepared in Comparative Example 1 and the semi-crystalline multi-component ceramic coating ( Figure 2 b) prepared in Example 1 after 20 days of high-temperature hydrothermal corrosion. ThroughFigure 2 It can be found that the locations where bulges or cracks appeared before hydrothermal treatment of the traditional ceramic coating, the bulges cracked, the crack width increased, and the length increased after hydrothermal treatment, which provided more pathways for the subsequent penetration of water vapor and oxygen, accelerating the corrosion failure of the coating and the substrate. After high-temperature hydrothermal corrosion of the semi-crystalline multi-element ceramic coating prepared in Example 1, the coating still maintained a high integrity, and formed a large number of flocculent products that could cover the surface, covering and filling some cracks, hindering the penetration of water vapor and oxygen, and delaying the corrosion of the metal substrate by water vapor.
[0055] Figure 3 and Figure 4 The electrochemical test results of the traditional ceramic coating prepared in comparative example 1 and the semi-crystalline multinary ceramic coating prepared in example 1 were carried out in 3.5wt.% NaCl solution. The corrosion resistance of the coating can be measured by the impedance value. Generally speaking, the larger the impedance value of the coating, the better its corrosion resistance. By comparing the Nyquist diagram and Bode diagram of the traditional ceramic coating and the semi-crystalline multinary ceramic coating, it can be found that the high-frequency capacitive reactance arc of the semi-crystalline multinary ceramic coating is greater than the capacitive reactance arc of the enamel coating, and the impedance modulus has a significant improvement, which indicates that the diffusion process of ions in the semi-crystalline multinary ceramic coating is hindered, the difficulty of ions penetrating the coating is increased, the density of the coating is greatly improved, and the corrosion resistance is significantly improved.
[0056] Example 2
[0057] This embodiment provides a method for preparing a semi-crystalline multi-element ceramic coating, comprising the following steps:
[0058] (S1) grinding the surface of the metal substrate with 600-grit sandpaper to remove the oxide layer, then ultrasonically cleaning with ethanol for 10 min, and drying in an oven at 75° C. for 30 min to obtain a pretreated metal substrate;
[0059] (S2) 51 parts of ZrO 2 、22 parts SiO 2 , 13 parts CaO, 4 parts TiO 2 , 2.1 copies K 2 O, 1.6 parts MnO 2 , 1.7 parts Fe 2 O 3 , 1.5 parts of BaO, 0.7 parts of CuO, 0.8 parts of ZnO, 0.5 parts of NiO, 2 parts of HfZrSiBCN and 0.15 parts of polyacrylic acid are mixed and ball milled (rotating speed is 2500r / min, time is 15min), and after ball milling, dried to constant weight to obtain a uniformly mixed semi-crystalline multi-element ceramic powder;
[0060] (S3) Put the semi-crystalline multi-component ceramic powder prepared in step (S2) and pure water into a conical flask according to a mass ratio of 1:0.3, and conduct mechanical stirring treatment (rotation speed is 500 r / min, time is 15 min). During the stirring process, add GP defoamer to obtain a semi-crystalline multi-component ceramic slurry;
[0061] (S4) Use the leveling method to evenly coat the semi-crystalline multi-component ceramic slurry in step (S3) on the surface of the metal substrate prepared in step (S1); then put it into an oven at 100 °C and dry for 20 min, and then put it into a box furnace at 825 °C for high-temperature sintering for 12 min to obtain a high-temperature hydrothermal corrosion-resistant semi-crystalline multi-component ceramic coating with good bonding to the metal substrate and high density. The coating thickness is about 300 μm.
[0062] Figure 5 XRD patterns of the semi-crystalline multi-component ceramic coating prepared in Example 2 and the traditional ceramic coating prepared in Comparative Example 1. Diffraction peaks of SiO 2 exist in both ceramic coatings. However, compared with the traditional ceramic coating, the diffraction peak intensity of the semi-crystalline multi-component ceramic coating is significantly reduced, and there is an obvious broad peak in the range of 20-40°, indicating an increase in the degree of amorphization.
[0063] Example 3
[0064] This example provides a preparation method of a semi-crystalline multi-component ceramic coating, including the following steps:
[0065] (S1) Polish the surface of the metal substrate with 800-mesh sandpaper to remove the oxide layer, then ultrasonically clean it with ethanol for 12 min, and put it into an oven at 70 °C and dry for 35 min to obtain a pretreated metal substrate;
[0066] (S2) Mix 49 parts of ZrO 2 , 24 parts of SiO 2 , 14 parts of CaO, 3 parts of TiO 2 , 2.5 parts of K 2 O, 2.2 parts of MnO 2 , 1.5 parts of Fe 2 O 3 , 2 parts of BaO, 0.6 parts of CuO, 0.9 parts of ZnO, 0.7 parts of NiO, 1.5 parts of ZrTiBCN and 0.18 parts of polycarboxylate, and then conduct ball milling treatment (rotation speed is 3000 r / min, time is 12 min). After the ball milling is completed, dry it to constant weight to obtain a uniformly mixed semi-crystalline multi-component ceramic powder;
[0067] (S3) Put the semi-crystalline multi-component ceramic powder prepared in step (S2) and pure water into a conical flask according to a mass ratio of 1:0.35 for mechanical stirring treatment (rotation speed is 350 r / min, time is 15 min). During the stirring process, add GPES defoaming agent to obtain a semi-crystalline multi-component ceramic slurry;
[0068] (S4) Use the leveling method to evenly coat the semi-crystalline multi-component ceramic slurry in step (S3) on the surface of the metal substrate prepared in step (S1); then put it into an oven at 105 °C for drying for 17 min, and then put it into a box furnace at 850 °C for high-temperature sintering for 10 min to obtain a high-temperature hydrothermal corrosion-resistant semi-crystalline multi-component ceramic coating with good bonding to the metal substrate and high density. The coating thickness is about 420 μm.
[0069] Example 4
[0070] This example provides a method for preparing a semi-crystalline multi-component ceramic coating, including the following steps:
[0071] (S1) Polish the surface of the metal substrate with 600-mesh sandpaper to remove the oxide layer, then ultrasonically clean it with ethanol for 10 min, and put it into an oven at 60 °C for drying for 50 min to obtain a pretreated metal substrate;
[0072] (S2) Mix 52 parts of ZrO 2 , 25 parts of SiO 2 , 11 parts of CaO, 6 parts of TiO 2 , 1.9 parts of K 2 O, 2.5 parts of MnO 2 , 2.1 parts of Fe 2 O 3 , 2.3 parts of BaO, 0.9 parts of CuO, 0.6 parts of ZnO, 0.8 parts of NiO, 0.8 parts of TiB N 0.25 parts of polycarboxylate, and then carry out ball milling treatment (rotation speed is 3500 r / min, time is 10 min). After the ball milling is completed, dry it to constant weight to obtain a uniformly mixed semi-crystalline multi-component ceramic powder;
[0073] (S3) Put the semi-crystalline multi-component ceramic powder prepared in step (S2) and pure water into a conical flask according to a mass ratio of 1:0.4 for mechanical stirring treatment (rotation speed is 500 r / min, time is 13 min). During the stirring process, add GPES defoaming agent to obtain a semi-crystalline multi-component ceramic slurry;
[0074] (S4) The semi-crystalline multi-component ceramic slurry in step (S3) is uniformly coated on the surface of the metal substrate prepared in step (S1) by the leveling method; then it is placed in an oven at 115 °C and dried for 10 min, and then placed in a box furnace at 775 °C for high-temperature sintering for 18 min to obtain a high-temperature hydrothermal corrosion-resistant semi-crystalline multi-component ceramic coating with good bonding to the metal substrate and high density. The thickness of the coating is about 600 μm.
[0075] Table 1 Porosity and standard protection current of semi-crystalline multi-component ceramic coatings and traditional ceramic coatings
[0076]
[0077] It can be found from Table 1 that the porosity of the semi-crystalline multi-component ceramic coatings prepared in Examples 1 to 4 is about 10% of that of the traditional ceramic coatings, and the standard protection current is reduced by two orders of magnitude compared with the traditional ceramic coatings, and the density of the semi-crystalline multi-component ceramic coatings is significantly improved.
[0078] The above description of the embodiments is to enable those of ordinary skill in the art to understand and use the invention. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative efforts. Therefore, the present invention is not limited to the above embodiments, and all improvements and modifications made by those skilled in the art without departing from the scope of the present invention as interpreted according to the present invention should be within the protection scope of the present invention.
Claims
1. A method for preparing a semi-crystalline multi-component ceramic coating, characterized in that: The following steps are involved: (S1) ball milling 48 to 52 parts of ZrO2, 20 to 25 parts of SiO2, 10 to 15 parts of CaO, 3 to 6 parts of TiO2, 1 to 3 parts of K2O, 1 to 3 parts of MnO2, 1 to 3 parts of Fe2O3, 1 to 3 parts of BaO, 0.5 to 1 part of CuO, 0.5 to 1 part of ZnO, 0.5 to 1 part of NiO, 0.5 to 2 parts of boride and 0.1 to 0.3 parts of a dispersant to obtain a semi-crystalline multi-element ceramic powder; (S2) dissolving the semi-crystalline multinary ceramic powder prepared in step (S1) in a solvent and mixing to obtain a semi-crystalline multinary ceramic slurry; (S3) coating the semi-crystalline multinary ceramic slurry prepared in step (S2) on the pretreated surface of the substrate, and sequentially performing drying treatment and high-temperature firing treatment to obtain a semi-crystalline multinary ceramic coating combined with the substrate.
2. The method for preparing a semi-crystalline multi-element ceramic coating according to claim 1, characterized in that: In step (S1), the boride is selected from one or more of TiB2, TiBN, ZrSiB6, ZrB2, ZrBN, HfB2, HfBN, ZrSiBCN, ZrTiBCN, HfZrSiBCN or HfZrTiBCN; The dispersant is selected from one or more of polymaleic acid, polyacrylic acid, polycarboxylate or maleic acid-acrylic acid copolymer.
3. The method for preparing a semi-crystalline multi-element ceramic coating according to claim 1, characterized in that: In step (S1), during the ball milling process, the rotation speed is 1500 to 4000 r / min and the time is 10 to 15 min.
4. The method for preparing a semi-crystalline multi-element ceramic coating according to claim 1, characterized in that: In step (S2), the mass ratio of the semi-crystalline multi-component ceramic powder to the solvent is 1:0.3-0.4; The mixing is performed by stirring, and a defoaming agent is added dropwise during the stirring process.
5. The method for preparing a semi-crystalline multi-element ceramic coating according to claim 4, characterized in that: The defoaming agent is selected from one or more of polyoxypropylene oxyethylene glycerol ether, polyoxypropylene glycerol ether, polyoxypropylene polyoxyethylene glycerol ether stearate, polypropylene glycol glycerol ether, polyether polyol or silicon polyether.
6. The method for preparing a semi-crystalline multi-element ceramic coating according to claim 1, characterized in that: In step (S3), the coating method is a leveling method; The pretreated substrate is specifically a substrate that is subjected to grinding, washing and drying treatments in sequence.
7. The method for preparing a semi-crystalline multi-element ceramic coating according to claim 1, characterized in that: In step (S3), during the drying process, the temperature is 100-115° C. and the time is 10-20 min; During the high temperature firing process, the temperature is 775-850°C and the time is 10-20 minutes.
8. The method for preparing a semi-crystalline multi-element ceramic coating according to claim 1, characterized in that: In step (S3), the thickness of the semi-crystalline multi-element ceramic coating is 100 to 600 μm.
9. A semi-crystalline multi-element ceramic coating, characterized in that: It is prepared by the method according to any one of claims 1 to 8.
10. Use of the semi-crystalline multi-element ceramic coating according to claim 9 in the field of aerospace.
Citation Information
Cited By
Ceramic heat-proof and heat-insulating coating as well as preparation and application thereof
CN122146166A